**Answer:**

Step 4 - Reason 4: **INVALID**

**Step-by-step explanation:**

This problem is a typical case of solving an algebraic expression of **one** **uknown variable**, which here is denoted with .

Let us first rewrite all information denoted in the question as follow:

**Given:**

**Step 1:** ** Reason 1: **<em>Given</em>

**Step 2:** ** Reason 2: **<em>Addition Property of Equality</em>

**Step 3:** ** Reason 3: **<em>Simplify</em>

**Step 4:** ** Reason 4: **<em>Division Property of Equality</em>

**Step 5:** ** Reason 5: **<em>Simplify</em>

Having obtained all solution steps we can conclude the following:

Step 1 - Reason 1: **Valid** because this is our given equation to be solved

Step 2 - Reason 2: **Valid** because this is a typical first step in such equations to eliminate our constants from the side (here the Left Hand Side) and have only our Uknown variables (in this case ).

Step 3 - Reason 3: **Valid** because we just compute the addition/subtractions on each side to simplify the expression

Step 4 - Reason 4: **INVALID** because at this point we already have one Unknown variable on the left and one constant on the right. So all we have to do is simplify the expression as it is. So here instead we should actually have:

⇔ ⇔⇔⇔

OR we could also solve it as:

⇔ ⇔ ⇔

Which essentially is Step 5 - Reason 5: **Valid** because of the computations just above.